Proceedings of the 2nd Symposium on Applied Perception in Graphics and Visualization 2005
DOI: 10.1145/1080402.1080423
|View full text |Cite
|
Sign up to set email alerts
|

A framework for comparing task performance in real and virtual scenes

Abstract: In this paper, we describe a framework for comparing task performance in real and virtual environments. Realistic graphics, rear projection, haptics and rapid prototyping are used to match the virtual scene to the real scene. We describe some preliminary placement tasks which were evaluated using eye-tracking and discuss our future plans for this framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Howlett et al [14] analyzed differences in task performance and eye movements on the same object sorting task performed in a real environment and a VR reproduction of the same environment using back-projection and a haptic input device. They found that their VR reproduction of reality -while quite close to the original -had some effects on the participants.…”
Section: Related Workmentioning
confidence: 99%
“…Howlett et al [14] analyzed differences in task performance and eye movements on the same object sorting task performed in a real environment and a VR reproduction of the same environment using back-projection and a haptic input device. They found that their VR reproduction of reality -while quite close to the original -had some effects on the participants.…”
Section: Related Workmentioning
confidence: 99%
“…The results from these studies indicate that there are correlations and many similarities between the two. However, it is not an easy task to design an empirical study to investigate this relationship (Howlett et al, 2005). In the Howlett study the respective times taken to complete tasks in the real and virtual worlds were compared in order to establish how well the virtual experience mimicked the real-world scenario.…”
Section: Digital Travel and Sense Of Placementioning
confidence: 99%
“…Furthermore, fixations are far more concentrated on moving virtual objects than on real ones. As a result, users in virtual environments generally look less around than in real environments [16].…”
Section: Hybrid Objects In Virtual Environmentsmentioning
confidence: 99%